An in Depth Analysis of Five Basic Sentence Patterns Plus Adjuncts In English Grammar - Syazwina, Zahfira; Audina, Nia; Indira, Indira; Munthe, Melda Veby Ristella (STABN RADEN WIJAYA WONOGIRI, 2024)
This research journal presents a comprehensive and systematic exploration of the five fundamental sentence patterns in English grammar—S-V, S-V-O, S-V-C, S-V-O-O, and S-V-O-C—with an additional focus on the function of adjuncts. The study was conducted over a five-month period with a group of senior high school students in Indonesia, analyzing how the understanding and mastery of sentence structures, alongside adjunct use, significantly impact syntactic awareness and written fluency. Each pattern is examined in terms of definition, function, structural characteristics, and usage through 15 examples (with and without adjuncts). The study employs both qualitative and quantitative methods to evaluate the effectiveness of targeted grammar instruction, offering insights into pedagogical implications for English language teaching. The findings confirm a marked improvement in students’ sentence variety and syntactic control, laying groundwork for advanced grammar instruction and curriculum planning.